A Bibliometric Analysis of Learning Organization (1976-2023) - Gema; Afriany, Dina; Japar , Muhammad (Kelola: Jurnal Manajemen Pendidikan, 2024)
This research aims to comprehensively examine scientific publications on 'learning organizations' through a bibliometric analysis of 1,551 scientific publications from 1976 to 2023, sourced from the Scopus database. Using a quantitative approach, this study focuses on two main aspects: performance analysis and science mapping. The bibliometric analysis follows the steps proposed by Donthu et al. (2021). The study highlights various metrics, including the number of publications and citations, subject areas, affiliations, universities, countries, prolific researchers, and influential documents. Additionally, it identifies recent research topics within the field. The findings show that publications and citations have increased over the last four decades, with significant growth starting in 1994 (24 publications) and peaking in 2020 (87 publications). Key findings include analyses of document types, source types, popular languages, subject areas, research trends, top countries, influential institutions, prolific authors, active sources, top keywords, and citation patterns. Notably, this research highlights the limitations inherent in using a single database (Scopus) for data collection.Finally, the study suggests directions for future research in learning organizations, providing valuable insights for scholars and practitioners in the field.